Resolution of Traffic Accident Cases Resulting in Death Through Restorative Justice (A Study at the Polrestabes Medan) - Bahajjad, Omar Abdul Rahman; Sitorus, Nanang Tomi (Rechtsvinding, 2025)
Traffic accidents that result in fatalities are tragic events that not only affect the victim and the perpetrator, but also the victim's family and the wider community. In an effort to achieve a more humane and just resolution, restorative justice approaches have been adopted as an alternative to formal court proceedings in criminal cases. This study aims to analyze the application of restorative justice by the Traffic Unit (Satlantas) of Medan City Police (Polrestabes Medan) in handling fatal traffic accident cases and identify the supporting and inhibiting factors in its implementation. This research uses normative juridical method with qualitative approach, supported by primary and secondary data collected through literature study and interviews with police officers and related stakeholders. The results showed that the implementation of restorative justice at Satlantas Polrestabes Medan involved a mediation process between the offender and the victim's family, with the participation of community leaders and under police supervision. Agreements reached usually include an apology, compensation, and a commitment to prevent future offenses. Supporting factors for this approach include mutual agreement between the parties and support from the community and law enforcement.